EFEKTIVITAS METODE ROLLENSPIEL DALAM PEMBELAJARAN MATERI POSSESSIVARTIKEL A1 BAHASA JERMAN - Mohamad Nur Fauzi; Lucky Herliawan Amalputra; Dani Hendra (Allemania, 2023)
Nouns and pronouns are important parts of speech when learning German. Both of them can be used as the subject, object, and adverb in the sentence. There are several rules regarding nouns in German, for instance, one of example of this type is Possessivartikel that used as a pronoun to express that something belongs to someone. Unfortunately, German learners especially in Indonesia face difficulties in learning Possessivartikel. the most factor is because the rules of Possessivartikel in Indonesian grammar is easier than the Possessivartikel’s rules in German grammar. In order to solve these problem, need a learning methods that can increase the students’ motivation and enhusiasm for the learning. Therefore, the Rollenspiel-method can be used in learning German. The purpose of this study was to find out: 1) the understanding of the possessivartikel by the students before using the Rollenspiel-method. 2) the understanding of the possessivartikel by the students after using the Rollenspiel-method. 3) the difference in students understanding of the Possessivartikel before and after using the Rollenspiel-method. 4) the effectiveness of the Rollenspiel-method in learning Possessivartikel German. This study used the pre-experiment with quantitative method. The population in this study was 30 students of class XII MIPA 1 in the 2022/2023 accademic year. The result showed that: 1) the understanding of the possessivartikel by the students before using the Rollenspiel-method is in the not good category. 2) the understanding of the possessivartikel by the students after using the Rollenspiel-method is in the good category. 3) There is a significant difference between the understanding of the Possessivartikel by the students before and after using the Rollenspiel-method. 4) the Rollenspiel-method is effective to be used in learning Possessivartikel German. This was proved by the results of the t-test calculation, that the significance value obtained is lower than 0,05. Based on the result of this study, the Rollenspiel-method can be used as an alternative in learning Possessivartikel.